2011
DOI: 10.12659/msm.881964
|View full text |Cite
|
Sign up to set email alerts
|

Oxycodone and Dexamethasone for pain management after tonsillectomy: A placebo-controlled EMG assessed clinical trial

Abstract: SummaryBackgroundSurface electromyographic (sEMG) study of post-tonsillectomy swallow-evoked muscular reactions was performed in order to evaluate the efficacy and safety of oxycodone and dexamethasone in pain management after tonsillectomy.Material/Methods90 randomly chosen operated adults were divided into three groups. Group 1 (n=30) was treated with OxyContin (Oxycodone) injections; Group 2 (n=30) was treated with Dexacort (Dexamethasone), and Group 3 (n=30) was a placebo group. Pain assessment included vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Despite the use of paracetamol and nonsteroidal anti‐inflammatory drug combination therapy children continue to suffer pain after adenotonsillectomy . Medications such as tramadol, codeine, morphine, oxycodone, and hydrocodone have all been used to supplement analgesia. Tramadol 1 mg/kg may have less potential to cause respiratory depression than equivalent doses of other opioid analgesics, but the drug's impact as a supplemental analgesic after adenotonsillectomy is poorly quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of paracetamol and nonsteroidal anti‐inflammatory drug combination therapy children continue to suffer pain after adenotonsillectomy . Medications such as tramadol, codeine, morphine, oxycodone, and hydrocodone have all been used to supplement analgesia. Tramadol 1 mg/kg may have less potential to cause respiratory depression than equivalent doses of other opioid analgesics, but the drug's impact as a supplemental analgesic after adenotonsillectomy is poorly quantified.…”
Section: Introductionmentioning
confidence: 99%
“…Persino et al [32] have suggested that acetaminophenhydrocodone prescription is therapeutically valuable in posttonsillectomy patients. Application of oxycodone reduces post-tonsillectomy pain [33] . However, this medication could depress ventilation and precipitate apnea to a larger extent in children with obstructive sleep apnea syndrome [34] .…”
Section: Opioidmentioning
confidence: 99%
“…Surgery was performed under general anaesthesia in 27 studies; in two studies the type of anaesthesia was not reported. 25,41 The surgical method was described in 19 studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Rescue analgesics were given in 25 studies, were not allowed in one study, 37 and information was not provided in three studies. 34,43,51 Study medications were administered before operation in eight studies, 29e31,45e49 before operation and intraoperatively in one study, 44 intraoperatively in seven studies, 8,26,34,35,38,43,50 intraoperatively and after operation in five studies, 27,32,36,37,39 after operation in seven studies, 23e25, 33,40,41,51 and before and after operation in one study. 44 One study compared intraoperative and postoperative administration of the study medication with placebo.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%